2020
DOI: 10.3390/ph13040066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles Using Odontosoria chinensis (L.) J. Sm. and Evaluation of their Biological Potentials

Abstract: The present study was aimed to synthesize silver nanoparticles (AgNPs) from the aqueous extracts of Odontosoria chinensis (L.) J. Sm. and the synthesized AgNPs were examined for their biopotentials. The Odontosoria chinensis extracts were added to 1 mM AgNO3 solution with different ratios viz., 0.5:9.5, 1:9, 1.5:8.5 and 2:8 ratios for the reduction of Ag ions. After reduction, the AgNPs of Odontosoria chinensis were analyzed spectroscopically for further confirmation. The synthesized AgNPs of Odontosoria chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…On the other hand, the human RBC membrane stabilization (HRBC) method has been employed for the determination of anti-inflammatory effects [24,25]. In this study, the results obtained indicated that the various S. unitus extracts, at various doses, exerted significant anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, the human RBC membrane stabilization (HRBC) method has been employed for the determination of anti-inflammatory effects [24,25]. In this study, the results obtained indicated that the various S. unitus extracts, at various doses, exerted significant anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, in recent years, medicinal plants have become a subject of interest for drug development owing to their phytochemical constituents and therapeutic potential. Few reports are available on the anti-inflammatory potential of pteridophytes [19][20][21][22][23][24][25]. Paulraj et al [26] reported the antibacterial ability of Sphaerostephanos subtruncatus and S. unitus, but no reports are available on the antioxidant, antidiabetic, anti-inflammatory, and cytotoxic effects of Sphaerostephanos unitus (L.) Holttum.…”
Section: Introductionmentioning
confidence: 99%
“…The complete reduction of Ag + ions occurred after 10 min at 40 °C. The synthesised AgNPs showed effective anti-inflammatory and antidiabetic activity, which was the result of the presence of polyphenols, terpenoids, and tannins in the extract, in addition to AgNP itself [ 175 , 178 ]. The amine groups present in the Capsicum annum proteins act as controlling and reducing agents for the formation of silver nanoparticles [ 179 ].…”
Section: Green Toxicology Of Silver Nanoparticlesmentioning
confidence: 99%
“…The biomass of Cinnamonomum camphora leaves treated with aqueous silver precursors at ambient temperature produces AgNPs with a circular shape. The protective and reducing biomolecules present in the plant are responsible for the shape of the nanoparticles [ 178 , 181 ]. Green synthesis using Mentha aquatica leaf extract produces small AgNPs.…”
Section: Green Toxicology Of Silver Nanoparticlesmentioning
confidence: 99%
“…The number of studies using plant extracts as reducing agents has been recently growing and various types of plant extracts have been used as reducing, capping, and stabilizing agents for the synthesis of AgNPs. Johnson et al [ 324 ] synthesized AgNPs using Odontosoria Chinensis extract and reported the formation of spherical AgNPs with diameters ranging from 22.3 to 48.2 nm. The reaction occurred at 40 °C, and a complete reduction of Ag + after 10 min was reported.…”
Section: Reviewmentioning
confidence: 99%